Improvement of Legal Measures to Prevent Crime with Regard to Minors in Kazakhstan - BAIMOLDINA, Svetlana M.; ZABIKH, Sholpan A. (Journal of Advanced Research in Law and Economics, 2017)
The relevance of this study is due to the problem of increasing crime among minors and against minors themselves. The purpose is to identify the characteristics of the victim's and deviant behavior of minors who commit offenses and themselves become victims of criminally punishable crimes in Kazakhstan and the Russian Federation. The leading approach to the study of this problem is the analysis of legal norms governing the rights and responsibilities of minors, the use of statistical information on the state of minors' delinquency and against minors themselves, and the study of the experience of leading legal scholars who have studied this problem. The study identifies the main trends in the victim's and deviant behavior of minors; develops methods to improve the criminal law provisions on liability for crimes committed against minors, as well as those minors who commit criminal offenses.  The materials of the article can be useful in the educational process in the study of problems related to the protection of children's rights, victim and deviant behavior of minors, as well as the prevention of violations in this area, the improvement of legal norms governing the rights and responsibilities of minors.